PERAN TASK BASED LEARNING (TBL) DALAM PEMBELAJARAN BAHASA INGGRIS - Ulupi Sitoresmi, Lusiana Dewi Kusumayati (Widya Wacana: Jurnal Ilmiah, 2015)
The research conducted to describe: (1) the role of task based learning (TBL) in teachingEnglish to the first semester students of MKU; (2) the procedures of TBL conducted by thelecturer on English subject; and (3) the strength and weaknesses of TBL applied on teachingEnglish subject. The research was conducted at Slamet Riyadi University Surakarta in theacademic year of 2014/ 2015. The result of the research shown four major findings which consistof: (1) the role of TBL; (2) the procedures of TBL; and (3) the strength and weaknesses of TBL.The research finding of this study indicates that task based learning gives contribution onteaching and learning activities in teaching English to the first semester students at MKUprograms. Moreover, based on research findings, it is expected that the lecturer will carefullymake preparatin before entering the classroom based on the students need, interest, and thestudents’ language competency. It is also expected that in learning language, the students shouldgive active participation by having interaction with others during the lessons and the for theother researchers who intended to conduct the research more detail about task based learning inteaching English subject, the researchers hope that the research findings can be used as areference for further research.Keywords: case study, task based learning, qualitative approaches, English learning.